Using Cognitively Accessible Survey Software on a Tablet Computer to Promote Self-Determination among People with Intellectual and Developmental Disabilities - Schwartz, Allen A.; Bacon, Ansley; O’Hara, David; Davies, Dan; Stock, Steven; Brown, Craig (Développement Humain, Handicap et Changement Social / Human Development, Disability, and Social Change)

(untitled) (Réseau International sur le Processus de Production du Handicap, 2015)
People with intellectual and developmental disabilities (I/DD) identify “speaking for oneself” as a highly salient aspect of self-advocacy and self-determination (SABE, 2011), yet limitations in cognition or language often limit their direct participation in surveys. This study describes a self-administered survey procedure that used supportive software on an iPad to create a survey interface that was easily navigable by respondents with I/DD. A survey based on items from the National Core Indicator (NCI) Adult Consumer Survey (HSRI & NASDDDS, 2001) was developed that included five items on choice-making which have been previously studied by Lakin et al. (2008) and Stancliffe et al. (2011). Cognitively diverse groups of self-advocates were recruited to take the iPad survey at both a national and state self-advocacy conference. The results indicated that the iPad survey platform enabled people with varying degrees of I/DD to respond independently to a self-administered survey with little training or assistance. The resulting iPad-gathered data on the NCI choice items supported the validity of the procedure by conforming to patterns from standard NCI interviews. This self-administered survey technology holds great promise for gathering many types of survey information directly from people with I/DD, allowing them to more actively participate in the design of supports, services, and environments that affect their lives.